2009
DOI: 10.1007/s00402-009-0886-9
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable microspherical implants containing teicoplanin for the treatment of methicillin-resistant Staphylococcus aureus osteomyelitis

Abstract: The in vitro and in vivo studies had shown that the TCP–PLGA microspheres were effective for the treatment of chronic osteomyelitis in an animal experimental model. Hence, these microspheres may be potentially useful in the clinical setting with the need for further investigation for optimal dosing of TCP–PLGA microspheres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…To induce 100% infection in osteomyelitis models, about 10 6 –10 8 CFU are required; in many studies ca. 2 × 10 6 CFU was used to stimulate osteomyelitis. ,, We used 4 × 10 6 and 8 × 10 6 CFU to develop severe osteomyelitis disease. On the basis of gross bone pathology analysis, extensive destructive lesions were observed in soft tissues with draining skin fistulas that had pus at the injured site.…”
Section: Discussionmentioning
confidence: 99%
“…To induce 100% infection in osteomyelitis models, about 10 6 –10 8 CFU are required; in many studies ca. 2 × 10 6 CFU was used to stimulate osteomyelitis. ,, We used 4 × 10 6 and 8 × 10 6 CFU to develop severe osteomyelitis disease. On the basis of gross bone pathology analysis, extensive destructive lesions were observed in soft tissues with draining skin fistulas that had pus at the injured site.…”
Section: Discussionmentioning
confidence: 99%
“…Most research focused on poly(lactide-co-glycolide) (PLGA). The in vitro and in vivo results of the related research showed that the antibiotic-PLGA microspheres were effective for the treatment of chronic osteomyelitis in animal experimental models [10][11][12]. In addition, Naraharisetti found that about 60% of gentamicin can be released from PLGA in approximately 5 to 6 days while the remaining drug is completely released in approximately 30 days [13].…”
Section: Introductionmentioning
confidence: 99%
“…Implant-related osteomyelitis (IRO) is a complex bone infection with methicillin-resistant S. aureus (MRSA) as the main causative organism [ [23] , [24] , [25] ]. Despite new antibiotic regimens, knowledge of the disease, and new material development, peri-prosthetic joint and intramedullary infections are still devastating and a challenging complication in total joint arthroplasty and fracture management with significant impact on our socio-economic system and a patient's life [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%